Synthesis and characterization of biobased epoxy monomers derived from d-glucose. (June 2015) - Rapi, Zsolt; Szolnoki, Beáta; Bakó, Péter; Niedermann, Péter; Toldy, Andrea; Bodzay, Brigitta; Keglevich, György; Marosi, György
Graphical abstract: Highlights: Epoxy monomers were successfully synthesized from d -glucose. The highest Tg value, comparable to that of DGEBA, was reached with the glucofuranoside-based formulation. The completion of curing is proved by Raman spectrometry. The thermal degradation of the biobased epoxy networks start at around 300 °C. Hardness values of the cured bioepoxy formulations are comparable to that of DGEBA. Abstract: This paper reports the preparation of newly synthesized sugar-based epoxy monomers, suitable for replacing petrochemical-derived epoxy resins of high thermal stability. Several bi- tri- and tetrafunctional epoxy components were prepared from d -glucose, among them the glucopyranoside- and glucofuranoside-based trifunctional ones proved to be the most promising for high-tech applications. The applicability of the synthesized compounds as epoxy monomers was investigated by curing probes with a model aromatic amine-type hardener. The curing enthalpy of the bioepoxy resins were examined, and compared to theoretical values, as well as the glass transition temperature, which is a crucial parameter when determining the potential fields of application of the bioresins. Tg values up to 175 °C were reached, while the thermal degradation of the cured resins start at around 300 °C.